The proper scope of behavioral law and economics - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2018)
Behavioral law and economics applies the conceptual tools of behavioral economics to the analysis of legal problems and legal intervention. These models, and the experiments to test them, assume an institution free state of nature. In modern societies, the law's subjects never see this state of nature. However a rich arrangement of informal and formal institutions creates generalized trust. If individuals are sufficiently confident that nothing too bad will happen, they are freed up to interact with strangers as if they were in a state of nature. This willingness dramatically reduces transaction cost and enables division of labor. If generalized trust can be assumed, simple economic models are appropriate. But they must be behavioral, since otherwise individuals would not want to run the risk of interaction.
Keywords: 330